Artificial Intelligence (AI) in Education: Unlocking the Perfect Synergy for Learning - Elkin Arturo Betancourt Ramirez, Juan Antonio Fuentes Esparrell (Educational Process: International Journal)
Background/purpose. Exploring intelligent agents in digital learning raises questions about the essence of Artificial Intelligence (AI) and its potential impact on education. This article provides insights into these inquiries and outlines outcomes from various experimental implementations, emphasizing the pivotal role of intelligent agents and conversational bots. These technologies have the power to revolutionize education by nurturing adaptive learning and problem-solving skills among university students. This work builds on existing research, aiming to articulate a conceptual understanding of AI as a strategic tool for learning.